Studies in The History and Tradition of Mount Ararat and Noah’s Ark - Avcı, Murat; Andreades, Sam A.; Sertesen, Cem; Başbaydar Belli, Filiz; Belli, Güzin Sühran (Academician Publishing Book DOI Portal, 2024)
-